Correlation of skeletal age by Greulich-Pyle atlas, physiological age by body development index, and dental age by London Atlas and modified Demirjian’s technique in children and adolescents of an Eastern Indian population - Champak Kumar Behera; Rachna Rath; Surya Narayan Das; Geeta Sahu; Gaurav Sharma; Archana Bhatta (Egyptian Journal of Forensic Sciences, 2023)
Abstract Background Forensic age estimation using multiple maturity indicators necessitates investigation of correlation between various techniques. This study intended to compare and evaluate the correlation between skeletal age using Greulich-Pyle atlas, dental age by Acharya’s modification of Demirjian’s technique and London Atlas method of Tooth Development, and age estimated by body developmental index with chronological age. Orthopantomograms and left hand-wrist radiographs of one hundred seventy-four subjects (64 males and 70 females) in the age group of 8–20 years were evaluated by age estimation methods. Physical parameters including height, weight, biacromial breadth, and biliospinale breadth were measured. The data were entered in the SPSS software (Version 27.0). Comparison between age estimation methods was done using Student’s t-test for paired samples. Unpaired t-test was utilized for gender-wise comparison of age. Pearson’s correlation coefficient was calculated to assess correlation between the various methods. Results Significant mean differences were noted between the chronological age and all the age estimation methods when Greulich-Pyle atlas method (− 0.43), modified Demirjian’s method (− 0.31), London Atlas Method (− 0.62), and body developmental index (− 0.51) were employed respectively. Inter-group comparison between all methods yielded no significant differences except for modified Demirjian’s method and London Atlas method (mean difference = 0.31). All the age estimation techniques showed strong correlation with chronological age; the best was provided by the Greulich-Pyle method (r = 0.92). Conclusion All the assessed age estimation techniques show strong correlation with chronological age. Acharya’s modified Demirjian’s method (dental age) and Greulich-Pyle atlas method (skeletal age) showed good accuracy and strong correlation with chronological age, suggesting that these methods can be used simultaneously and/or interchangeably for age assessment in children and adolescents of Eastern Indian population.